Measurement of the production cross section of prompt Ξ_c^0 baryons in p–Pb collisions at √s_NN = 5.02 TeV - Trubnikov, Vyacheslav; The ALICE collaboration (The European Physical Journal C, 2025)
The transverse momentum (p_T) differential production cross section of the promptly produced charm-strange baryon Ξ_c^0 (and its charge conjugate anti-Ξ_c^0) is measured at midrapidity via its hadronic decay into π^+ Ξ^- in p–Pb collisions at a centre-of-mass energy per nucleon–nucleon collision √s_NN = 5.02 TeV with the ALICE detector at the LHC. The Ξ_c^0 nuclear modification factor (R_pPb), calculated from the cross sections in pp and p–Pb collisions, is presented and compared with the R_pPb of Λ_c^+ baryons. The ratios between the p_T-differential production cross section of Ξ_c^0 baryons and those of D^0 mesons and Λ_c^+ baryons are also reported and compared with results at forward and backward rapidity from the LHCb Collaboration. The measurements of the production cross section of prompt Ξ_c^0 baryons are compared with a model based on perturbative QCD calculations of charm-quark production cross sections, which includes only cold nuclear matter effects in p–Pb collisions, and underestimates the measurement by a factor of about 50. This discrepancy is reduced when the data